My dad's computer a conservation with Internet security expert William R. Cheswick. - Cherry, S. (IEEE spectrum)
This paper presents an interview with William R. Cheswick, a leading Internet security expert and chief scientist at the NJ-based provider of network intelligence, Lumeta Corp.